The Potency of Ginkgo Biloba in Treating Tinnitus: A Review - Daniel Yakin Eliamar Aritonang (Eureka Herba Indonesia, 2022)
Extracts of Ginkgo biloba leaves are used for medicinal purposes for at least 5000 years in China. More recently Ginkgo biloba extracts have been used in Western countries. In the USA, Canada and the UK extracts are widely available as nonprescription food supplements. In France and Germany, a standardized dry leaf extract is registered as a drug and is commonly prescribed for. Several studies have been conducted to measure the usefulness and properties of Ginkgo Biloba in connection with the treatment of Tinnitus. This literature review aims to identify the components and the mechanism of action of Ginkgo Biloba in the treatment of tinnitus. The articles selected were all published within the past five years from PubMed. 11 articles were obtained and were included in the review. Based on the articles, The most important active chemical compounds in Ginkgo Biloba are flavonoids (ginkgo-flavone glycosides) and terpenoids (ginkgolides A, B, C, J, and bilobalide). Gingko Biloba has vasoregulatory effect, antagonism of platelet activator factor, antioxidant activity, enhance neuroplasticity and inflammatory. In conclusion, Ginkgo Biloba demonstrated effectiveness in the treatment of tinnitus, through the significant improvement in self-perception of tinnitus loudness and severity.